Towards a sustainable management model of the “Festa dos Tabuleiros” - Braga, José Luís; Camponês, André; Coelho, João Pinto; Pereira, Miguel; Silva, Óscar Lima (European Spatial Research and Policy, 2023)
The key goal of this conceptual paper is the creation of a sustainable management model of the Festa dos Tabuleiros (FT) event that provides a quality experience to the visitors without threatening the social, cultural and environmental integrity of the territory. Action research methodology has been used to improve the way the Tomar municipality organises and promotes the FT. In order to establish this model, it is necessary to determine the agents and relationships that underlie the production system of this event, aiming to improve the quality of its offer and the experience it provides to visitors as well as the sustainability of its production and consumption processes. In this sense, the development of the model will be based on four tasks: (1) stock-taking, interpreting and exhibiting cultural resources; (2) identifying, involving, analysing and educating stakeholders; (3) benchmarking of good practices in event sustainability; and (4) managing and monitoring the model. Hence, this paper aims to contribute to the safeguarding of the FT and to the sustainable development of the municipality and the region. This intent is achieved through the creation of a sustainable tourist-cultural management model that promotes the study, protection, enhancement, and dissemination of this event, as well as the creation of efficient and innovative solutions in an integrated way.